The shared decision making of older adults in healthcare. Issue 2 (8th January 2019) - Pusey, Emilia; Tinker, Anthea; Lucivero, Federica
Abstract : Purpose: The research question is: what are older adults' experiences of shared decision making (SDM) in a healthcare setting? This involved exploring older adults' experiences and opinions of decision making in a healthcare setting, and understanding what SDM means to older adults. The paper aims to discuss this issue. Design/methodology/approach: A qualitative study using face-to-face, semi-structured interviews with adults over 65 years was conducted. Thematic analysis was used. Findings: Three broad themes were identified which ascribed roles to individuals involved in decision making. This includes the way in which older adults felt they should be involved actively: by asking questions and knowing their own body. The doctors' role was described as assistive by facilitating discussion, giving options and advice. The role of the family was also explored; older adults felt the family could impact on their decisions in both a direct and indirect way. There was some confusion about what constituted a decision. Research limitations/implications: This was a small qualitative study in a market town in England. Practical implications: Clinicians should facilitate the involvement of older adults in SDM and consider how they can increase awareness of this. They should also involve the family in decision making. Originality/value: There are limited studies which look at this issue in depth.